2018
DOI: 10.5633/amm.2018.0413
|View full text |Cite
|
Sign up to set email alerts
|

Open Comminuted Expressed - Depressed Skull Fracture

Abstract: Skull fractures occur as the result of the effect of kinetic forces and represent discontinuity of the bones of the skull. They can be opened and closed affecting tissues; linear, diastatic, comminuted affecting cranial level; or depressed ones often leading to injuries of meninx, brain tissue with different types of intracranial bleeding. The paper presents a 56-year old male patient who suffered severe craniocerebral injury of the frontal region including orbit while operating the wood processing machine. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…This is not much different from previous studies which stated that surgery was performed in 90.72% of cases either for reasons of eliminating compression of the fracture segment in the brain, removing fractures from the dura, or cosmetics, and preventing the risk of infection. 9,[11][12][13] In this study, it was found that the most length of stay was 5-10 days. This is because in cases of depressed calvaria fractures, close monitoring must be carried out, especially in cases of depressed calvaria fractures that are often followed by the presence of other intracranial abnormalities, which of course will prolong the length of stay of the patient.…”
Section: Resultsmentioning
confidence: 97%
“…This is not much different from previous studies which stated that surgery was performed in 90.72% of cases either for reasons of eliminating compression of the fracture segment in the brain, removing fractures from the dura, or cosmetics, and preventing the risk of infection. 9,[11][12][13] In this study, it was found that the most length of stay was 5-10 days. This is because in cases of depressed calvaria fractures, close monitoring must be carried out, especially in cases of depressed calvaria fractures that are often followed by the presence of other intracranial abnormalities, which of course will prolong the length of stay of the patient.…”
Section: Resultsmentioning
confidence: 97%